2022
DOI: 10.4103/jcas.jcas_197_20
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum toxin for scalp dysesthesia

Abstract: Scalp dysesthesia is characterized by abnormal cutaneous sensations such as burning, stinging, or itching of the scalp. This condition is particularly challenging to manage as there is a lack of well-established treatments. By limiting release of neurotransmitters such as substance P, glutamate, and calcitonin gene-related peptide, botulinum toxin may have a role in ameliorating neuropathic pain. We report a unique case in which botulinum toxin was used in the management of scalp dysesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…Our findings are consistent with previous reports of the successful use of off-label BTX as a potential treatment modality for patients struggling with trichodynia [5,7]. Trimboli et al pioneered the first use of BTX for the treatment of trichodynia and relied on a dose of 200 units.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings are consistent with previous reports of the successful use of off-label BTX as a potential treatment modality for patients struggling with trichodynia [5,7]. Trimboli et al pioneered the first use of BTX for the treatment of trichodynia and relied on a dose of 200 units.…”
Section: Discussionsupporting
confidence: 92%
“…Off-label BTX has been shown in multiple, randomized, placebo-controlled studies to be an effective treatment modality in the management of various neuropathic disorders including plantar fasciitis, focal painful neuropathies, mechanical allodynia, and myofascial pain [12][13][14]. It has been postulated that BTX may directly inhibit neurogenic inflammation via an inhibitory effect on the release of various neurotransmitters from afferent nerve fibers responsible for eliciting the pain sensation including substance-P, calcitonin gene-related peptide, and glutamate [5,7,[12][13][14]. The exact mechanism of action of BTX in diminishing the pain response is yet to be fully understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 2 case reports describing 2 patients with scalp pain treated with BTX-A. 28,29 In one patient with diffuse scalp dysesthesia, split-scalp injections of BTX-A (40 units) and normal saline resulted in less pain on the side treated with BTX-A at the 8-week follow-up, although improved symptoms of both scalp hemispheres were noted. 28 Another patient with multiple painful cutaneous piloleiomyomas noted a rapid decrease in pain after injections with BTX-A (200 units) every 3 months.…”
Section: Scalp Painmentioning
confidence: 99%
“…The mechanism of action of BoNT-A is presumably due to blocking the release of acetylcholine from peripheral nerves, thereby reducing vasodilatation of the cutaneous blood vessels [ 42 , 43 ]. Other neurotransmitters were also suggested that could be reduced by BoNT-A injection, including substance P, calcitonin gene-related peptide, and glutamate [ 44 ].…”
Section: Reviewmentioning
confidence: 99%